The psychometric properties of the Persian version of the MUSIC Model of Academic Motivation Inventory among nursing students - Mansoureh Ashghali Farahani; Maryam Saeedi (Wiley, 2022)
Abstract Aim To determine the psychometric properties of the Persian version of the MUSIC Inventory in nursing students. Design Cross‐sectional psychometric study. Methods Transcultural adaptation of the MUSIC Model of Academic Motivation Inventory was carried out using translation to Persian and back‐translation. Then, the qualitative and quantitative face and content validity of the inventory were evaluated. Construct validity was assessed by exploratory factor analysis. To perform construct validity and reliability, a convenience sample of 360 undergraduate nursing students was recruited. Cronbach's alpha was used to assess internal consistency reliability. Results Cronbach's alpha for all items of the MUSIC inventory was .94, and each factor was between .72-.93. Exploratory factor analysis supported the 5‐factor structure of the MUSIC inventory. These 5 factors explain 66.59% of the overall extracted variance. Three items of the MUSIC inventory, which were related to the empowerment component, were deleted. Conclusion Based on the findings of this study, the Persian version of the MUSIC Model of Academic Motivation Inventory is a valid and reliable tool for Persian language nursing students.